Aplication of Radakng House Design in Bus Terminal at Malinau North Kalimantan with Neo-Vernacular Approach - Amba, Rocky; Purnama, Muhammad Sega Sufia (Cultural Syndrome, 2021)
Malinau Regency is an expansion of Bulungan Regency. Over time, the economic growth of the Malinau community has accelerated and mobility movements have also increased. Various plans have been established by the local government. The position of Malinau City is very strategic to connect the surrounding regencies and areas around Malinau whose territory is directly adjacent to Malaysia. The required terminal is a type-A terminal. With the diversity of cultures and customs in Malinau Regency, the questions in this research are (1) How to design a terminal that can represent the culture of the Malinau people and (2) How to approach the application of these cultures into the design. This research has never been raised before, which is to raise the culture and wisdom of Malinau Regency into a building with an urban context. The method used is Literature Review, which is by collecting local cultural sources related to the design of traditional community buildings, then with Neo-vernacular theory will be applied to new building elements in the terminal design. The result achieved in this research is a new terminal design with a Neo-vernacular Architecture approach seen from the urban context, facade appearance and proper zoning